Revealing the Role, Mechanism, and Impact of AlF3 Coatings on the Interphase of Silicon Thin Film Anodes. Issue 41 (26th August 2022) - Adhitama, Egy; van Wickeren, Stefan; Neuhaus, Kerstin; Frankenstein, Lars; Demelash, Feleke; Javed, Atif; Haneke, Lukas; Nowak, Sascha; Winter, Martin; Gomez‐Martin, Aurora; Placke, Tobias
Abstract: Silicon (Si) holds great promise as an anode material for high energy density lithium ion batteries owing to its theoretical capacity of up to 3579 mAh g −1 . However, this potential comes at the expense of major challenges, because the solid electrolyte interphase (SEI) at Si anodes hardly provides long‐term protection due to severe volume expansion. Yet, when it comes to the SEI, the formation mechanism is not thoroughly understood. Here, thin AlF3 coatings are deposited on Si thin film to stabilize the SEI. To evaluate the SEI, systematic observation utilizing X‐ray photoelectron spectroscopy is performed at different (de‐)lithiation states, allowing stage‐by‐stage analysis to reveal the role, mechanism, and impact of AlF3 coating. Results show that the capacity retention is significantly improved for 90% after 100 cycles. The transformation of AlF3 into Li‐Al‐F compounds, as confirmed by ion chromatography, is responsible for an enhanced performance due to its high ionic conductivity. Moreover, the SEI of coated Si thin films is rich in inorganic species (i.e., LiF) which is beneficial to prevent electrons to pass through. This work will deepen the understanding of SEI on Si anodes with respect to the coating approach, suggesting future directions to improve coating layers on Si. Abstract : This study reports the role, mechanism, and impact of AlF3 coating on Si thin film anodes. The observations are done in different (de‐)lithiation states by utilizing X‐ray photoelectron spectroscopy and ion chromatography with conductivity detection. The transformation of AlF3 to LiAlF is responsible for increased stability. These results suggest shifting the research direction toward functional coatings on Si thin films.